2007
DOI: 10.1007/s00410-007-0272-y
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology of fluid-induced eclogite and amphibolite facies metamorphic reactions in a subduction–collision system, Bergen Arcs, Norway

Abstract: Rb-Sr multimineral isochron data for metamorphic veins allow to date separate increments of the mineral reaction history of polymetamorphic terranes. Granulite facies rocks of the Lindås nappe, Bergen Arcs, Norway, were subducted and exhumed during the Caledonian orogeny. The rocks show petrographic evidence for two distinct events of local fluid infiltration and vein formation, along fractures and shear zones. The first occurred at eclogite facies (15-21 kbar, 650-750 °C) and a later one at amphibolite facies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 73 publications
2
103
0
Order By: Relevance
“…(1) Growth or partial or complete recrystallization of mica (Willigers et al 2004;Glodny et al 2008;Villa 2010). Of the samples presented in this study, all micas and feldspars show evidence of dynamic recrystallization, and are therefore interpreted as recording metamorphic or deformational ages unless otherwise stated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Growth or partial or complete recrystallization of mica (Willigers et al 2004;Glodny et al 2008;Villa 2010). Of the samples presented in this study, all micas and feldspars show evidence of dynamic recrystallization, and are therefore interpreted as recording metamorphic or deformational ages unless otherwise stated.…”
Section: Resultsmentioning
confidence: 99%
“…The Rb-Sr system in micas has been shown to be robust to temperatures greater than 600°C over orogenic timescales (>15 Ma), provided the rock is free of fluids (e.g. Glodny et al 2008). We therefore consider it unlikely that white mica ages relate to cooling through a specific closure temperature, as isotopic equilibrium is more likely to be achieved by fluid-induced recrystallization than by temperature-driven diffusional processes.…”
Section: Resultsmentioning
confidence: 99%
“…1), dated at 405 Ma (Young et al 2007), and 430 Ma eclogites in the Lindås Nappe in the Middle Allochthon (Glodny et al 2008) share a broadly similar tectonic history with the WGC eclogites: all were derived from Baltica and were formed from subduction of the Baltica margin during its final collision with Laurentia. In contrast, 452 Ma eclogite formation in the Tromsø Nappe in the Uppermost Allochthon ( Fig.…”
Section: Introductionmentioning
confidence: 96%
“…It has also been demonstrated that fluids in HP metamorphic rocks play a key role in promoting equilibration of isotopic systems used as geochronometers (Glodny et al, 2003(Glodny et al, , 2008. In turn, some isotopic systems may still record the effects of previous seafloor alteration or the isotopic signature of the precursor rock (Halama et al, 2010(Halama et al, , 2011John et al, 2011;Miller et al, 1988;Putlitz et al, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…7B) also suggest Sr isotope homogenization. Homogenization of Sr isotopes by HP fluid-rock interaction was previously recognized for eclogite-and amphibolite facies fluid infiltration events and used to date HP fluid-rock interaction (Glodny et al, 2003(Glodny et al, , 2008. The existence of the FTS 4 isochron strongly points to a metasomatic fluid infiltration event that caused resetting of the isotopic system in the Tian Shan pillow metabasalts because of two reasons: First, from seawater alteration alone a wide range of initial Sr isotope compositions would be expected, as observed for seawater-altered eclogites (e.g., Miller et al, 1988;Halama et al, 2011).…”
Section: Constraints From Sr-nd Isotopes On Seafloor Alteration and Tmentioning
confidence: 99%